2021
DOI: 10.1530/eje-20-0862
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical characteristics of isolated forms of central precocious puberty: a cohort study at a single academic center

Abstract: Objective: Isolated central precocious puberty (CPP) includes sporadic, familial and adoption-related forms, and the characterization of its etiology is challenging. This study investigated the prevalence and clinical characteristics of isolated CPP. Design and Methods: This observational cohort study included all patients (n=395) with CPP included in the database of a single academic pediatric care center over a period of 11.5 years. Results: In total, 332 of the 395 patients (84%) had isolated forms of CP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 37 publications
0
12
0
2
Order By: Relevance
“…A recent large French study from single center confirmed a low proportion of boys presenting with idiopathic CPP, while this diagnosis occurred in the majority of girls (Table 3) [17]. The onset of puberty seems to be earlier in organic than in idiopathic CPP in both sexes [1][2][3]17]. Albeit the odds of detecting an underlying pathology are very high in boys with a very early presentation of pubertal findings, there is consensus that all boys with CPP should undergo brain imaging to exclude a central cause [27].…”
Section: Etiologymentioning
confidence: 84%
See 1 more Smart Citation
“…A recent large French study from single center confirmed a low proportion of boys presenting with idiopathic CPP, while this diagnosis occurred in the majority of girls (Table 3) [17]. The onset of puberty seems to be earlier in organic than in idiopathic CPP in both sexes [1][2][3]17]. Albeit the odds of detecting an underlying pathology are very high in boys with a very early presentation of pubertal findings, there is consensus that all boys with CPP should undergo brain imaging to exclude a central cause [27].…”
Section: Etiologymentioning
confidence: 84%
“…No change in the incidence of male CPP after accounting for the increase in the clinic volume during the period 2001-2010 was documented [16]. A recent large French study from single center confirmed a low proportion of boys presenting with idiopathic CPP, while this diagnosis occurred in the majority of girls (Table 3) [17]. The onset of puberty seems to be earlier in organic than in idiopathic CPP in both sexes [1][2][3]17].…”
Section: Etiologymentioning
confidence: 95%
“…In a recent issue of the European Journal of Endocrinology, Harbulot et al . ( 11 ) reported how they performed the first test of the mismatch hypothesis, by analysing their single-centre cohort of girls with isolated variants of central precocious puberty ( n = 319) in an unprecedented way: they distinguished three subgroups and calculated the Z-scores of birthweight-for-gestational-age and BMI-at-diagnosis-of-central-precocious-puberty in each subgroup. Their findings ( Fig.…”
mentioning
confidence: 99%
“…BMI at diagnosis of CPP is expressed in centiles for sex and chronological age. The authors of the original paper ( 11 ) distinguished three subgroups of girls with isolated CPP. In the 'familial' subgroup (red), the average centile rose from 50 (weight at birth) to 96 (BMI at diagnosis of CPP), for an upward mismatch of 46 centiles.…”
mentioning
confidence: 99%
See 1 more Smart Citation